Feasibility and acceptability of technology-based caregiver engagement strategies delivered in a summertime childhood obesity prevention intervention: results from an internal pilot of the Camp NERF (Nutrition, Education, Recreation, and Fitness) study - Hopkins, Laura C. (Pilot Feasibility Stud, 2018)
BACKGROUND: The most efficacious childhood obesity prevention interventions have involved caregivers directly or indirectly. Due to the high reliance on technology, research examining technological intervention approaches is warranted, particularly during the summer when parents may be more difficult to engage and the risk for excess weight gain among children is high. METHODS: The feasibility and acceptability of a multi-component childhood obesity prevention intervention incorporating a caregiver component utilizing technology-based approaches—texting and social media—was explored. This was an internal pilot of the Camp Nutrition Education Recreation and Fitness (NERF) study, a group RCT for school-age children coupled to the USDA Summer Food Service Program. Feasibility and acceptability of the technology caregiver engagement component were assessed via process outcomes (participation rates) and in-depth interviews. RESULTS: Participants (n = 37) were 91.9% female, 91.8% Black, 58.7% low-income, and 75.0% overweight/obese. Participation rates in texting and social media were 62.2% and < 3%, respectively. Themes emerged from the in-depth interviews were texting provides connection; desire more involvement with program; fear social media privacy intrusion. CONCLUSIONS: Results will be used to inform changes to technology-based caregiver engagement strategies to be tested in future interventions. TRIAL REGISTRATION: Clinical Trials, NCT02908230/09-19-2016. Registered 20 September 2016